A mediating effect of food Neophobia toward purchasing intention of goat milks among Malaysian consumers - Kok-Siew H.; Rahman H.B.A.; Rahman Z.B.A.; Mohd L.L.-C.; Asmaddy Haris (Serials Publications, 2024)
Indexed by Scopus